2018
DOI: 10.1186/s40659-018-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-382 inhibits cell growth and migration in colorectal cancer by targeting SP1

Abstract: BackgroundEmerging evidence showed that microRNAs (miRs) play critical roles in human cancers by functioning as either tumor suppressor or oncogene. MIR-382 was found to function as tumor suppressor in certain cancers. However, the role of MIR-382 in colorectal cancer (CRC) is largely unknown. Specificity protein 1 (SP1) is highly expressed in several cancers including CRC and is correlated with poor prognosis, but it is unclear whether or not MIR-382 can regulate the expression of SP1.MethodsMIR-382 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…SP1 play major roles in the pathogenesis of various cancers. Consistent with this, one study showed that silencing of SP1 inhibited growth and migration and attenuated the effect of miR-382 inhibitor on colorectal cancer cell behaviors (Ren, Zhang & Jiang, 2018). Also, SP1-induced lncRNA terminal differentiation-induced ncRNA (TINCR) was significantly increased in colorectal cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…SP1 play major roles in the pathogenesis of various cancers. Consistent with this, one study showed that silencing of SP1 inhibited growth and migration and attenuated the effect of miR-382 inhibitor on colorectal cancer cell behaviors (Ren, Zhang & Jiang, 2018). Also, SP1-induced lncRNA terminal differentiation-induced ncRNA (TINCR) was significantly increased in colorectal cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 55%
“…SP1, a well-known transcription factor, is implicated in an ample variety of essential biological processes, such as cell growth, differentiation, apoptosis, and carcinogenesis via activating the transcription of many cellular genes that contain putative CG-rich SP-binding sites in their promoters. Of note, there was limited information for the correlations of CCAT1, miR7-5p, and SP1, although SP1 has been reported to regulate many other lncRNA and/or miRNAs in cancer cells (Jin, Zhang, Hu, Zhang, Guo & Feng, 2019;Li, Qiu, Sun, Zhang & Wang, 2019;Ren, Zhang & Jiang, 2018). Thus, the mechanisms underlying the connections among these molecules remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The mature gene locus were chr14:101,054,316-101,054,337, and the base sequence was GAAGUUGUUCGUGGUGGAUUCG , with a length of 22 nt. (Fig.1) 2.1.2 hsa-miR-382-5P participates in disease regulation Using PubMed to retrieve the related literature of miR-382-5P, we found that miR-382-5P was upregulated in acute promyelocytic leukemia [7,8] , atherosclerosis [12] ,breast cancer [4] ,epidural fibrosis [10] , primary myelofibrosis [9] , primary liver cancer [11] ,cervical cancer [13] , but down-regulated in glioma [5,6] ,oral squamous cell carcinoma [3] ,miR-382 was down-regulated in non-small cell lung cancer [14,15] , osteosarcoma [16] , prostate cancer [19] ,ovarian cancer [20] , primary liver cancer [24] , colorectal cancer [21,22] , while schizophrenia [25] ,diabetic nephropathy [17] , IgA nephropathy [18] ,infantile hemangioma [23] . Thus, the expression of miR-382-5P is tissue-specific, and it is involved in the regulation of cell viability, migration, invasion, angiogenesis, proliferation, cell differentiation, oxidative stress and other biological behaviors.…”
Section: Data Analysis Of Tcga Databasementioning
confidence: 99%
“…A series of nucleases obtained mature miR-382-5P and miR-382-3P by cutting and editing miR-382, in which miR-382-5P was located in the long arm of chromosome 14. In recent years, many studies have shown that the expression of miR-382-5P is abnormal in oral squamous cell carcinoma [3] ,breast cancer [4] ,glioma [5,6] ,acute promyelocytic leukemia [7,8] ,primary myelofibrosis [9] ,epidural fibrosis [10] ,primary liver cancer [11] ,atherosclerosis [12] ,cervical cancer [13] ,miR-382 is abnormal in non-small cell lung cancer [14,15] , osteosarcoma [16] , diabetic nephropathy [17] , IgA nephropathy [18] prostate cancer [19] ,ovarian cacner [20] ,colorectal cancer [21,22] ,infantile hemangioma [23] ,primary liver cancer [24] ,schizophrenia [25] , which are closely related to the proliferation, differentiation, migration, invasion, drug resistance and other biological processes of tumor cells. However, the expression and clinical significance of miR-382-5P in ovarian cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, COUP-TFII is at the center of a miRNA network that elegantly explain the loss of EMT. MiR-382 is an onco-suppressor in non-small-cell lung, ovarian, prostate and esophageal cancers [189][190][191][192], and it is downregulated in colorectal cancer where it inhibits tumor metastasis, blocking SP1, and sensitizes cancer cells to chemotherapy [193,194]. Interestingly, COUP-TFII potentiates the action of SP1 in angiogenesis and development [92,94], recognizing SP1 response elements and miR-382 directly binds COUP-TFII 3 -UTR, knocking down the receptor, and hence downregulates two transcription factors that are demonstrated to synergize and induce EMT.…”
Section: The Gastrointestinal Cancers: Mostly An Oncogenementioning
confidence: 99%